2019
DOI: 10.17094/ataunivbd.441972
|View full text |Cite
|
Sign up to set email alerts
|

Cirit Atlarında İnfluenza A Virus Enfeksiyonunun Serolojik ve Moleküler Yöntemlerle Araştırılması

Abstract: Öz: İnfluenza A virus (IAV) insan, at, kanatlı ve birçok memeli türünü enfekte eden, zoonotik karakterli ve oldukça bulaşıcı solunum sistemi patojenidir. Bu çalışmada, geleneksel cirit sporunun yaygın olarak yapıldığı Erzurum ilinde solunum sistemi hastalığı belirtileri gösteren atlarda influenza A virusun serolojik ve moleküler yöntemlerle araştırılması amaçlanmıştır. Bu amaçla Atatürk Üniversitesi Veteriner Fakültesi Hayvan Hastanesi'ne getirilen 57 at çalışmaya dâhil edilmiştir. Herhangi bir aşı geçmişi olm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These mentioned events are very common in rural areas, which increases the chance of being exposed to vectors like ticks. Thus, it is crucial to study infectious agents that can be detected in or transmitted by these animals, for the benefit of both animal and human health (Alkan et al 2013, Aydin et al 2020, Gilbride et al 2021Timurkan et al 2019). The reason that the seroprevalence of CCHFV infection is so high in this study is due to a number of factors, including hot weather conditions, global warming, the existence of asymptomatic animals, a continuous movement of hosts in and out of these regions, their living conditions, and the fact that horses or donkeys are kept together with other livestock.…”
Section: Resultsmentioning
confidence: 99%
“…These mentioned events are very common in rural areas, which increases the chance of being exposed to vectors like ticks. Thus, it is crucial to study infectious agents that can be detected in or transmitted by these animals, for the benefit of both animal and human health (Alkan et al 2013, Aydin et al 2020, Gilbride et al 2021Timurkan et al 2019). The reason that the seroprevalence of CCHFV infection is so high in this study is due to a number of factors, including hot weather conditions, global warming, the existence of asymptomatic animals, a continuous movement of hosts in and out of these regions, their living conditions, and the fact that horses or donkeys are kept together with other livestock.…”
Section: Resultsmentioning
confidence: 99%
“…EHV-2 causes immunosuppression, keratoconjunctivitis, pharyngitis, ulcerative lesions of the oral mucosa, upper respiratory tract signs, and poor race performance (19), whereas EHV-5 may cause upper respiratory tract signs and equine multinodular pulmonary fibrosis (38). Equine influenza virus (EIV), member of the Orthomyxoviridae family, causes severe respiratory disease, and infected horses show characteristic clinical signs of the disease, such as pyrexia, dyspnoea, anorexia, and coughing (47).…”
Section: Occurrence Of Selected Parasites and Viral Infections In Hor...mentioning
confidence: 99%
“…The highest overall rate for EIV was found in the Marmara region (60%), where the present study was also performed, and the seropositivity for horses (41%) was more than four times as high as it was for donkeys (9%). According to Timurkan and Aydin (47), the seropositivity for antibodies to EIV in jereed horses in the province of Erzurum in eastern Turkey amounted to 26.3%, but they could not detect virological positivity. In the present study, the virological presence of EIV was revealed in 3% of horses and 1% of donkeys.…”
Section: Componentmentioning
confidence: 99%
See 1 more Smart Citation